Antiviral activity of TMC435 monotherapy in patients infected with HCV genotypes 2-6: TMC435-C202, a phase IIa, open-label study - Moreno C. (2017)
Background & Aims: TMC435 is an investigational, once-daily, oral NS3/4A protease inhibitor currently in phase III development for the treatment of hepatitis C virus (HCV) infection. Phase I and II studies in patients infected with HCV genotype 1 have demonstrated that TMC435 is generally well tolerated, has a pharmacokinetic profile that supports once daily dosing, and demonstrates potent antiviral activity. This phase IIa study (TMC435-C202; NCT00812331) was conducted to investigate the antiviral activity, safety, tolerability, and pharmacokinetics of TMC435 in treatment-nave patients infected with HCV genotypes 2-6. Methods: The study consisted of 7 days of monotherapy with TMC435 (200 mg once daily). Patients could begin treatment with pegylated interferon/ribavirin from day 8 with a follow-up period up to days 37-42. Results: Thirty-seven patients were enrolled in Germany, Belgium and Thailand. For the primary end point at day 8, the mean (± standard error) change in plasma HCV ribonucleic acid (log 10 IU/ml) from baseline was the greatest for genotypes 6 (-4.35 ± 0.29) and 4 (-3.52 ± 0.43), followed by genotypes 2 (-2.73 ± 0.71) and 5 (-2.19 ± 0.39). No antiviral activity was evident for genotype 3. Viral breakthrough occurred in six patients during the monotherapy phase and in six additional patients during PegIFN/RBV-only period. All adverse events were mild or moderate and there were no discontinuations during the TMC435 monotherapy period. Conclusions: The results of this phase IIa proof-of-concept trial provide evidence that TMC435 has a spectrum of activity against multiple HCV genotypes, except for genotype 3. In this study, TMC435 was generally safe and well tolerated. © 2012 European Association for the Study of the Liver. Published by Elsevier B.V. All rights reserved.